Herramientas tecnológicas y su influencia en el aprendizaje interactivo en los estudiantes de la Escuela España, Puebloviejo. 2022 - Vera Barros, María Belen (2023)
The research of this project is called technological tools and their influence on interactive learning in the Escuela Fiscal España del Cantón Puebloviejo, so that in class hours they can share the development of skills and abilities in students. The theoretical foundations concerning the two variables were extracted and detailed in detail. It is necessary to recognize the importance of the use of ICT's in the teaching work, however in their pedagogical work little use of them is observed, they are also aware that innovating in their classes with technology would improve the teaching and learning processes in their students, as well as other tools could be used to evaluate the processes in the students of the institution. Demonstrating the need to use technological tools that facilitate interactive classes for teachers to strengthen educational areas. A descriptive and explanatory research was used to verify the factors that affect the improvement of the teaching-learning process. The application obtained great benefits by providing training workshops in the basic programs of the Office package such as: Word, Excel, Power Point, as well as the Internet, which has become a necessity for education and no longer a luxury. The research was able to demonstrate how the use of technological tools, conceived an efficient learning with the motivation and enthusiasm to learn on the part of all teachers.